HYDRO-GEOSYNERGETIC BIOGENIC-MANTLE HYPOTHESIS OF HYDROCARBON ORIGIN AND ITS INVOLVEMENT INTO DIRECT PROSPECTING TECHNOLOGY JUSTIFICATION - Bagriy, I.; Starodubets, K.; Gordieieva, Yu.; Semenyuk, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In accordance with circuit of substance in nature, hydrogeosynergetic biogenic-mantle hypothesis of hydrocarbon origin was elaborated and consequently, direct prospecting structural-thermal-atmo-hydro-geochemical technology (STAHGT) was constructed. For the first time, considered technology was applied and implemented in the process of prospecting works both at ground-level oil-and-gas bearing facilities of Ukraine (Dnieper–Donets depression) and at off-shore facilities of Black Sea (the north-western and north-eastern shelf) via use of specifically developed hardware systems. Taking into account location of existing fields in the catchment of Sula River, comprehensive hydrological studies were conducted. The quantitative characteristics of biogenic methane within the catchment areas and underflow deposits were defined. The contents of biota, methane, as well as the thickness of the underlying sediments within the riverbed have been determined. As a result, zones of enhanced permeability were allocated. Within these zones infiltration afflux of water-dissolved substrates are formed. It was determined that hydrocarbons and their projections, located in degassing pipes of deposits in the valley of Sula River, are of mantle origin. The proposed unified approach enables to substantiate the search criteria of petroleum potential in areas where there are neither deflection zones nor thick sedimentary cover, but there are favorable conditions for hydrocarbons accumulation in crystalline rocks. Based on a unified technology STAHGT, recommendations for further studies to substantiate new petroleum-bearing areas and facilities are provided. For the first time, the sources of replenishment of oil and gas deposits in operation were substantiated.
Keywords: hydro-geosynergetic biogenic-mantle hypothesis; hydrocarbons; hydrocarbon migration; tectonics